Inhibitory Effects of Ethanol Extracts from Nuruk on Oxidative Stress, Melanogenesis, and Photo-Aging - Lee, Sang-Jin (The Korean Society of Mycology, 2012)
Nuruk contributes to the unique characteristics of Korean alcoholic beverages. In this study, the effects of nuruk extracts (NE) on anti-oxidant characters, melanogenesis, and anti-photoaging activity were investigated. NEs were obtained from the 70% ethanol extracts of six types of nuruk, which have been used in brewing of fermented alcohol beverages in Korea. First, various antioxidant characteristics were identified in terms of 2,2'-azino-bis(3-ethylbenzthiozoline-6-sulphonic acid) (ABTS) radical scavenging activity, superoxide dismutase (SOD) expression, and inhibition of xanthine oxidase activity. NE#4 exhibited potent ABTS radical scavenging activity (IC(50) = 19.51 µg/mL). Compared with NE#4, relatively lower levels of activity were observed for NE#3 and NE#6, with IC(50) values of 90.99 and 76.88 µg/mL, respectively. According to results of western blot analysis for determination of SOD expression in H(2)O(2)-treated HepG2 cells, NE#5 and NE#6 induced a dramatic increase in the expression ratio of SOD, compared to the group treated with H(2)O(2) only. Activity of xanthine oxidase, which converts xanthine into uric acid, generating superoxide ions, was inhibited by NE#4 and NE#6 in a dose-dependent manner. NE#4 induced significant inhibition of mushroom tyrosinase activity. A reduction in cellular melanin contents of 80% was observed in B16F1 melanocytes treated with NE#5 and NE#6; these effects were similar to those of arbutin at 100 µM. In addition, gelatin zymography and reverse transcription-PCR analysis were performed for assessment of anti-photoaging activity of Nuruk. Treatment with NE#6 resulted in dramatically inhibited activities of matrix metalloproteinase (MMP)-2/-9, suppressed expression of MMP-1, and increased expression of type-1 procollagen. Results of gelatin zymography for NE#4 and NE#5 were similar, to a slightly lesser degree. These results suggest the potential of NE#4 and NE#6 as natural ingredients for use in functional foods and cosmetics.